تطبيق منهجية UNHabitat في تقدير إسهام المحافظات في الناتج المحلي الإجمالي واختبار دالة الفروق بينها "دراسة تطبيقية موازنة بين المحافظات السورية" - روماني, هدى (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف البحث إلى بيان كيفية تطبيق منهجية المنظمة الدولية UNHabitat في تقدير متوسط إسهام المحافظات في الناتج المحلي الإجمالي لعام 2009، وقياس متوسط إسهام الأنشطة الاقتصادية على مستوى المحافظة في تكوين الناتج المحلي الإجمالي. كما يهدف البحث لاختبار معنوية الفروق بين متوسطات إسهام المحافظات, وكذلك بين متوسطات إسهام الأنشطة الاقتصادية بتطبيق نموذج تحليل تباين ذي التصنيف الثنائي (Two way ANOVA). وقد استند البحث إلى بيانات مسح قوة العمل لعام 2009, وشمل المسح 15195 أسرة. وقد تضمنت نتائج البحث متوسط إسهام كل نشاط اقتصادي ونسبته على مستوى المحافظة ومساهمته في الناتج المحلي الإجمالي، ومتوسط نصيب الفرد، ونسب إسهام الأنشطة الاقتصادية في الناتج المحلي الإجمالي على مستوى القطر. إذ حسبت جميعها وفق منهجية UNHabitat، وقد كانت تلك النتائج متقاربة مع ما يماثلها في نظام الحسابات القومية. كما أظهرت نتائج اختبار تحليل التباين (Two way ANOVA) تبايناً جوهرياً بين المحافظات في مدى إسهامها في الناتج المحلي الإجمالي, إذ كانت إسهامات المحافظات: حلب, وريف دمشق, ودمشق, الأعلى في تكوين الناتج المحلي الإجمالي بالإضافة إلى أن إسهام كل من الأنشطة الاقتصادية: الزراعة, والصناعة, وتجارة الجملة, والمفرَّق، هي إسهام جوهري في تكوين الناتج المحلي الإجمالي. The research aims to apply the methodology of the international organization Unhabitat in estimating the average contribution of the governorates to the gross domestic product (GDP) of year 2009, and to measure the average of the economic activities contribution at the level of each governorate in creation of the gross domestic product, also it aims to test significance of differences among averages of the governorates contribution and among averages of the economic activities contribution through applying two way ANOVA, and the research depends on labor force survey data of year 2009 where the survey included 15195 families. the research results included mean and ratio contribution of each economic activity at the governorate level in the gross domestic product, and the average per capita and ratio contribution of economic activities in the GDP at state level, where all calculated according to UNHabitat methodology, these results were similar to the ones of national accounts system, also the results of the analysis of variance test (Two way ANOVA) showed significant differences among governorates in their contribution to GDP, where the contributions of governorates: Aleppo and Rural Damascus and Damascus, were the highest in the GDP, also the contribution of each of the economic activities: agriculture, industry and wholesale & retail trade are essential to the GDP.